Simulation, design, and implementation of waveguide-to-coaxial transitions - Ejercito, Bianca Sorella C. (2011)
Waveguide-to-coaxial transitions are used to connect waveguide applications to equipment that use coaxial cables for interconnections. In this undergraduate student project, simulation of waveguide-to-coaxial transitions was conducted in the aim of characterizing the effects of these transitions in measurement steups involving them. Microwave Studio from Computer Simulation Technology (CST) was used to simulate the waveguide-to-coaxial transitions. The effect of varying certain parameters on return loss, insertion loss, and bandwidth was examined. Optimal measurements for the parameters were also identified. The project aims to set the foundation for future work on waveguide-to-coaxial transitions in general in the Philippines. The project also aims to generate efficient and flexible designs that will allow local RF and microwave components and systems businesses to engage in the manufacture of these devices.